(untitled) (Northern International Medical College Journal, 2022)
Background: Craniofacial anthropometric values and indices are vital for experts from different walks of science. Variations in such values are evident in racial and geographical attribute. Furthermore, anthropological classification would assist clinicians in planning regional surgeries, forensic identification and many more. Objective: In this study we aimed to measure the head-face landmarks in a particular population and to correlate their association. Methodology: To assess intra population variation, the fronto-occipital circumference, facial height, bizygomatic breadth, bitragion breadth, bigonial breadth, width of mouth, intercanthal width, biocular breadth and body height of 100 Bangladeshi women (age 25-45 years) were measured and craniofacial indices were calculated. Frequencies were observed while comparing the variables by ANOVA using SPSS version 17. Result: The mean values of facial indices revealed as prosopic index 103.8 ± 12cm, zygomandibular index 81.1 ± 7.44cm, canthal index 36.93 ± 2.3cm and circumference-interorbital index 2.26 ± 0.4cm. 86% of subjects were clustered to hyperleptoprosope group (very narrow face) and 69% had wide jaw with closely placed eyes. No significant (p>0.05) correlation was denoted between variables and facial indices. Conclusion: The result of this study would provide an access to baseline data of local standards for anthropometric evaluation which might help the clinicians in planning regional surgeries and forensic experts in identification. Northern International Medical College Journal Vol. 12 No.1 July 2020, Page 503-506